G625 Collaboration between community child health and child/adolescent mental health services in the UK: results from a national survey. (25th October 2020) - Ayyash, HF; Ogundele, MO; Schumm, T; Mitrofan, O
Abstract : Aims: Neurodevelopmental and Emotional problems (NDEP), including behavioural and emotional problems, such as Attention Deficit Hyperactivity Disorder, Autism Spectrum Disorder, Tics disorder/Tourettes syndrome, Learning Disorders, developmental delay and development coordination disorder are commonly managed in the UK by the Community Child Health (CCH) Paediatricians, often working within integrated specialist teams with allied health, social and educational professionals. Children and young people with NDED have three to four-fold increase in prevalence of co-occurring mental health disorders into adulthood. The current picture of integration between CCH and Child and Adolescent Mental Health (CAMH) services in the UK is mixed and complex. We aimed to explore the experiences of CCH Paediatricians about working jointly with local CAMH services. Method: An online survey was conducted among CCH Paediatricians using a modified Child and Adolescent Psychiatrists Surveillance System (CAPSS) survey questionnaire, as part of a validation survey of CAPSS. The CAPSS focuses on surveillance of rare psychiatric conditions and CCH clinicians are considered to be able to play an important role in case ascertainment. Results: A total of 245 respondents working within 180 CCH units across the UK completed the questionnaire, including Consultants (75%), Specialist Associates (19.5%) and Trainees (5%). Only 27 respondents (11.6%) reported working with young people aged 19–25 years, often due to their complex disabilities, special education placement, delayed transition or lack of suitable adult services. Participating Paediatricians' experiences suggest great variation in service provision and configuration for children of various ages and diagnosis across the UK. The commonest themes identified included increasing rate of CCH referrals from primary healthcare/other agencies as default, patients' experience of service fragmentation/bouncing between CCH and CAMHS. They also highlighted their challenges and desirability of joint- working with CAMHS. Conclusion: The re are compelling historical and logical reasons to support a wider integration between CCH and CAMHS as optimal settings for providing effective and seamless high quality care to most children presenting with various MH and Neurodevelopmental disorders. Responses highlight the wide range of work CCH paediatricians are undertaking in the field of CYP mental health and therefore have essential roles in contributing to psychiatric surveillance.